Consensus on Land Use Change in Bangka Tengah Regency - Anik Endah Puspitasari; Retno W. D. Pramono (Universitas Gadjah Mada, 2022)
Differences in perception or interest in land use can potentially lead to conflict. One of the efforts to minimize the possibility of conflicts in land use is to build consensus among stakeholders. This process is not only able to minimize conflict but is expected to be the most appropriate solution to facilitate the implementation of the plan. This paper will present an example of the dynamics of consensus building in the process of land conversion in Bangka Tengah Regency which had previously been designated as a mining zone and then planned to be converted into a Tourism Special Economic Zone (Tourism SEZ). In this proposal, an agreement has been successfully built between the first permit holder and the SEZ proposer, however, the plan to establish SEZ has not materialized. What exactly is a factor in this so that the agreement that has taken place has not become the capital for the successful implementation of the plan? This research aims to explain the constraints on not implementing the plan after an agreement has been reach. The research was conducted with a stakeholder mapping analysis framework. Data were obtained by conducting interviews, observations, and collecting documents related to the SEZ proposal. The selection of informants was carried out purposively to obtain detailed information so that it could be used to answer research questions. The results showed that there were factors that become obstacles in planning implementation, related to the consensus that was successfully built. The imperfect consensus that has been successfully built can be seen in the incomplete pouring of commitments in contracts between stakeholder, thus making the consensus reached a pseudo-consensus.